Galectins, Eosinophiles, and Macrophages May Contribute to Schistosoma japonicum Egg-Induced Immunopathology in a Mouse Model - Ye, Zhanhong; Huang, Shiguang; Zhang, Yanxia; Mei, Xu; Zheng, Huanqin; Li, Meiyu; Chen, Jianhuang; Lu, Fangli (Frontiers in Immunology, 2020)
Schistosomiasis is a severe public health problem, which can cause tissue fibrosis and even be fatal. Previous studies have proved that galectins and different kinds of cells involve in the regulation of tissue fibrosis process. In this study, Kunming outbred mice were infected with Schistosoma japonicum (S. japonicum). Our results showed that compared with uninfected mice, there were severe egg granulomatous inflammation and tissue fibrosis in the livers, spleens, and large intestines of S. japonicum-infected mice at 8 weeks post-infection (p.i.), and the number of eosinophils by hematoxylin and eosin staining and CD68 macrophage positive area by immunohistochemical staining were significantly increased. Detected by using quantitative real-time reverse transcription-polymerase chain reaction (qRT-PCR), at 8 weeks after S. japonicum infection, the mRNA expression levels of galectin (Gal)-1, Gal-3, CD69, eosinophil protein X (EPX), and chitinase 3-like protein 3 (Ym1) were significantly increased in liver, spleen, and large intestine; eotaxin-1 (CCL11) and eosinophil cationic protein were significantly increased in both liver and spleen, eotaxin-2 (CCL24) and Arginase1 (Arg1) were significantly increased in both spleen and large intestine, and CD200R was significantly increased in both liver and large intestine. However, interleukin (IL)-1ß and inducible nitric oxide synthase (iNOS) were only significantly increased in liver. The M2/M1 ratio of CD200R/CD86 genes was significantly increased in liver, and ratios of Ym1/IL-1β and Ym1/iNOS were significantly increased in liver, spleen, and large intestine of S. japonicum-infected mice. Ex vivo study further confirmed that the levels of Gal-1, Gal-3, CD200R, Arg1, and Ym1 were significantly increased, and the ratios of CD200R/CD86 and Ym1/IL-1β were significantly increased in peritoneal macrophages isolated from S. japonicum-infected mice at 8 weeks p.i. In addition, correlation analysis showed that significant positive correlations existed between mRNA levels of Gal-1/Gal-3 and EPX in liver, between Gal-3 and Ym1 in both liver and large intestine, and between Gal-3 and CD200R in peritoneal macrophages of S. japonicum-infected mice. Our data suggested that Gal-1, Gal-3, eosinophils, and macrophages likely involve in the development of egg granulomatous response and fibrosis induced by S. japonicum infection.